2013
DOI: 10.1055/s-0033-1343406
|View full text |Cite
|
Sign up to set email alerts
|

Knee and Hip Joint Biomechanics are Gender-specific in Runners with High Running Mileage

Abstract: Female runners are reported to be more prone to develop specific knee joint injuries than males. It has been suggested that increased frontal plane joint loading might be related to the incidence of these knee injuries in running. The purpose of this study was to evaluate if frontal plane knee and hip joint kinematics and kinetics are gender-specific in runners with high mileage. 3D-kinematics and kinetics were recorded from 16 female and 16 male runners at a speed of 3 m/s, 4 m/s, and 5 m/s. Frontal plane joi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
25
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(30 citation statements)
references
References 14 publications
4
25
1
Order By: Relevance
“…The time-course profiles of the hip and knee joint moments in the INT obtained in this study were similar to those of able-bodied subjects (Gehring, 2014). According to Gehring (2014), the hip joint in able-bodied subjects was typically in an adducted position during running, as the foot must be placed almost directly beneath the center of mass of the body in the frontal plane.…”
Section: Discussionsupporting
confidence: 76%
“…The time-course profiles of the hip and knee joint moments in the INT obtained in this study were similar to those of able-bodied subjects (Gehring, 2014). According to Gehring (2014), the hip joint in able-bodied subjects was typically in an adducted position during running, as the foot must be placed almost directly beneath the center of mass of the body in the frontal plane.…”
Section: Discussionsupporting
confidence: 76%
“…This literature has been more focused, with much of it analyzing lower limb posture during landing, knee and hip loading, or hip muscle activation. Compared with males, females generally appear to land with more knee extension [24] and have greater peak hip adduction and internal rotation [9,[25][26][27][28] as well as greater gluteal muscle activation [9,29]. Most of these differences have been preliminarily attributed to the sexual dimorphism of the human pelvis [30][31][32].…”
Section: Introductionmentioning
confidence: 99%
“…Bam et al (3) further suggested that females have an advantage over longer distances because they are more resistant to fatigue than their male counterparts. Potential explanatory factors include anthropometric sex differences, the effects of reproductive hormones in females and sex differences in substrate utilization (6), tendon characteristics (21) and running biomechanics (8). Conversely, the capacity for females to maintain running speed better than males as race distance increases has not been established in ultra-trail running races (UTRR) (13).…”
Section: A C C E P T E D Introductionmentioning
confidence: 99%